The practice of corporate communication in crisis management: a local case study - Qindeel, Rabia; Bidin, Noriah; Mat Daud, Yaacob (2006)
The potential of laser-induced plasma is now becoming an important for fusion research in attempt to add the source of energy. Light energy can create plasma when high irradiance is focused. However, until today scientists and engineers still work hard to get the fusion energy into reality. Hence research is still going on to endeavor the knowledge and better understanding on laser plasma. In order to give some light on the problems, a fundamental study was carried to form the laser plasma. In this case, a high-power Q-switched Nd:YAG laser was employed to generate plasma. Camera lenses with various focal lengths were utilized to generate optical breakdown and initiate plasma plume on a cylindrical brass target. The plasma plume formation were visualized and recorded via CCD video camera. The recorded images were analyzed using Matrox Inspector version 2.1 and video test 5 softwares. The results obtained show that, the plasma area is linearly increased with focal length, which is in good agreement with the beam waist concept. Whereas, the length of plasma, related to the Rayleigh range was found quadratically change with focal length.